(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
This article examines the manifestation and development of national values across historical periods. It argues that, although values are diverse in nature, the human being – human life, rights, freedom, and well-being – stands as the highest value. The article analyzes the revival of the Uzbek people’s material, spiritual, and historical values after independence, the interrelationship between national and universal values, and the dynamic, changing character of values under shifting economic, political, and cultural conditions. It emphasizes that a nation builds its future on the historical experience of its ancestors rather than on borrowed templates.